Effect of Degumming Performed with Different Type Natural Soaps and Through Microwave Energy Method on The Properties of Silk Fiber - Yuksek, Metin (Asian Journal of Chemistry, 2011)
Removal of sericin on the silk fibers is a surface modification process. Various chemical agents are used in the sericin removal process. In this article, effect of the sericin removal process performed in order to clear of the fiber surface from sericin through conventional and ultrasonic methods by using natural materials such as olive oil, daphne, turpentine soaps. The results obtained were examined with percentage weight loss values; bleaching properties, mechanical properties, morphological characteristics (SEM) followed by FT-IR. The most weight loss was observed in the sericin removal process performed with daphne and turpentine soaps through the microwave method. In all samples, microwave had a role in the highness of both the tensile strength and elongation values. Bleaching level was higher in the methods where microwave was used.